The Copyright Infringement In Cinematography - Andini, Putri (Universitas Internasional Batam, 2017)
The drama entitled ?Kau Yang Berasal Dari Bintang? produced by SinemArt and aired by RCTI TV station on 28 April 2014 was claimed as a plagiarism of  the most popular South Korean drama